Pengawasan Penggunaan Kendaraan Dinas di Dewan Perwakilan Rakyat Daerah (DPRD) Provinsi Sumatera Barat - Aisyah Putri Gutawa; Rahmadhona Fitri Helmi (PUBLICNESS: Journal of Public Administration Studies, 2026)
This study examines the supervision of official vehicle usage at the Regional House of Representatives (DPRD) of West Sumatra Province within the framework of regional asset management. Although regulatory provisions mandate monitoring and control, the implementation of supervision remains predominantly administrative and has not yet functioned as an operational control system. This research employs a qualitative descriptive approach with a phenomenological perspective. Data were collected through semi-structured interviews, observations, and document analysis involving the DPRD Secretariat, the Regional Financial and Asset Management Agency, the Inspectorate, and DPRD leadership. Data validity was ensured through source and technique triangulation, while analysis followed the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that supervision has not been carried out effectively due to the absence of technical standards, the lack of performance-based evaluation mechanisms, and weak corrective actions. Supervision is limited to inventory recording, maintenance reporting, and tax administration without monitoring operational use, usage frequency, or accountability of users. Furthermore, the absence of periodic reporting obligations and audit indicators prevents early detection of misuse. Consequently, supervision has not yet contributed to improving transparency and accountability in regional asset management. Strengthening operational standards, evaluation systems, and institutional follow-up mechanisms is necessary to transform administrative supervision into a comprehensive managerial control system.